CRISPR/Cas12a Mediated Genome Editing Enhances Bombyx mori Resistance to BmNPV - Dong, Zhanqi; Qin, Qi; Hu, Zhigang; Zhang, Xinling; Miao, Jianghao; Huang, Liang; Chen, Peng; Lu, Cheng; Pan, Minhui (Frontiers in Bioengineering and Biotechnology, 2020)
CRISPR/Cas12a (Cpf1) is a single RNA-guided endonuclease that provides new opportunities for targeted genome engineering through the CRISPR/Cas9 system. Only AsCas12a has been developed for insect genome editing, and the novel Cas12a orthologs nucleases and editing efficiency require more study on insects. We compared three Cas12a orthologs nucleases, AsCas12a, FnCas12a, and LbCas12a, for their editing efficiencies and antiviral abilities. The three Cas12a efficiently edited the Bombyx mori nucleopolyhedrovirus (BmNPV) genome and inhibited BmNPV replication in BmN-SWU1 cells. The antiviral ability of the FnCas12a system was more efficient than that of the SpCas9 system after infection by BmNPV. We created FnCas12a×gIE1 and SpCas9×sgIE1 transgenic hybrid lines and evaluated the gene-editing efficiency of different systems at the same target site. We improved the antiviral ability using the FnCas12a system in transgenic silkworm. This study demonstrated the use of the CRISPR/Cas12a system to achieve high editing efficiencies, and increase disease resistance in the silkworm.